Role of janus kinase inhibitors in the treatment of alopecia areata - Triyangkulsri K; Suchonwanit P (Dove Medical Press, 2018)
Korn Triyangkulsri, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand Abstract: Alopecia areata (AA) is a common hair loss disorder worldwide with characteristic exclamation mark hairs. Although AA is self-limited, it can last for several months or even years in some patients. Currently, there is no US Food and Drug Administration-approved treatment for AA. Many off-label treatments are available but with limited efficacy. Through a better understanding of molecular biology, many targeted therapies have emerged as new alternatives for various autoimmune diseases. Various janus kinase (JAK) and signal transducer and activator of transcription (STAT) proteins form signaling pathways, which transmit extracellular cytokine signals to the nucleus and induce DNA transcriptions. By inhibiting JAK, T-cell-mediated inflammatory responses are suppressed. Increasing evidence suggests that JAK inhibitors (JAKis) are effective in the treatment of many autoimmune diseases, including AA. Among these, several studies on tofacitinib, ruxolitinib, and baricitinib in AA had been published, demonstrating promising outcomes of these agents. Unlike oral formulations, efficacy of topical forms of tofacitinib and ruxolitinib reported in these studies is still unsatisfactory and requires improvement. This review aims to summarize evidence of the efficacy and safety of JAKis in the treatment of AA. Keywords: baricitinib, JAK, JAK inhibitors, JAK-STAT pathway, ruxolitinib, tofacitinib